Efektivitas Tablet Bacillus thuringiensis H-14 Isolat Salatiga terhadap Jentik Aedes aegypti pada Dua Sumber Air yang Berbeda - Arum Triyas Wardani; RA. Wigati; Esti Rahardianingtyas; Rendro Wianto; Arief Nugroho (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2021)
Dengue Hemorrhagic Fever (DHF) is a vector-borne disease that is still a health problem in Indonesia. One of the DHF control effort is to control the larvae of the mosquito vector using Bacillus thuringensis H-14. The weakness of this metode is its short residual effect. This study aims to determine differences in the effectiveness of B. thuringiensis H-14 tested in two different water sources, namely well water and PDAM water in people's houses and its residual effects in the field. The study used a quasi-​experimental, which include laboratory and field experiments in March to September 2017. The research was carried out by producing B. thuringensis H-14 Salatiga isolates in the form of slow release tablets, testing the efficacy and measuring their effectiveness to Aedes aegypti mosquito larvae in two kinds of water sources. The results showed that the content of B. thuringiensis Salatiga isolate in slow release tablets weighing 125 mg was 5 mg. The efficacy test at laboratory scale showed that the LC50 was 0.436 ppm and the LC90 was 2.440 ppm. The effectiveness test in the field of LC50 (PDAM water) is 0.098 ppm and (well water) is 1.909 ppm, while LC90 (PDAM water) is 0.186 ppm and (well water) is 0.909 ppm. The efficacy assay results showed there was no significant difference in the effect of B. thuringiensis tablet between well water and PDAM water. B. thuringiensis H-14 tablets were effective in controlling Ae. aegypti larvae more than 80% until the 7th day in field testing.